2007
DOI: 10.1177/0011128707306017
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Gangs

Abstract: Research and theory about female gang involvement remain scarce. Drawing on the National Longitudinal Study of Adolescent Health, this study addresses whether males and females differ in risk factors associated with gang membership (e.g., community characteristics, parent-child relationships, associations with deviant friends). Integrating theory and research from social disorganization, social control, and feminist perspectives on crime/ delinquency, few differences are found between boys and girls in terms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Several studies utilizing in-depth interviews have provided insight into the experience of female gang membership and have highlighted areas of significance, including risk factors of victimization and poor family relationships (Miller, 2001; Molidor, 1996). Additionally, quantitative studies, although limited in their numbers, have identified shared risk factors for gang membership among males and females (Bell, 2009; Hill, Howell, Hawkins, & Battin-Pearson, 1999; Howell & Egley, 2005). Overall, female adolescent delinquency and antisocial behaviors are predicted by a cumulative risk model that includes family dysfunction, maltreatment history (Kroneman, Loeber, & Hipwell, 2004), and a history of physical and/or sexual abuse (Graves, 2007; McKnight & Loper, 2002; Wright, Friedrich, Cinq-Mars, Cyr, & McDuff, 2004).…”
Section: Risk Factors: Victimization History and Family Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies utilizing in-depth interviews have provided insight into the experience of female gang membership and have highlighted areas of significance, including risk factors of victimization and poor family relationships (Miller, 2001; Molidor, 1996). Additionally, quantitative studies, although limited in their numbers, have identified shared risk factors for gang membership among males and females (Bell, 2009; Hill, Howell, Hawkins, & Battin-Pearson, 1999; Howell & Egley, 2005). Overall, female adolescent delinquency and antisocial behaviors are predicted by a cumulative risk model that includes family dysfunction, maltreatment history (Kroneman, Loeber, & Hipwell, 2004), and a history of physical and/or sexual abuse (Graves, 2007; McKnight & Loper, 2002; Wright, Friedrich, Cinq-Mars, Cyr, & McDuff, 2004).…”
Section: Risk Factors: Victimization History and Family Relationshipsmentioning
confidence: 99%
“…National estimates indicate approximately 4% of all children are reported to child welfare agencies as alleged victims of abuse (U.S. Department of Health and Human Services, Administration on Children, Youth & Families, 1999); in contrast, studies have shown that 39% of female juvenile offenders have been victims of abuse or neglect in substantiated reports (Pawaserat, 1991). Additionally, longitudinal studies have demonstrated that being abused or neglected as a child increases the likelihood of being arrested as an adolescent by 59% (Goodkind, Ng, & Sarri, 2006;Herrera & McCloskey, 2001), and young women involved in gangs, when compared with male gang members, have a disproportionately higher history of physical and sexual abuse (Bell, 2009). More recent studies have provided overwhelming evidence that sexual abuse for women and girls presents an increased risk for engagement in antisocial behaviors more generally (Javdani, Sadeh, & Verona, 2011).…”
Section: Victimization Experiencesmentioning
confidence: 99%
“…It is worth noting that while each unique indicator and associated construct are reported under only 1 table, some of the constructs and indicators may be linked to more than 1 risk or protective factor. For example, social disorganization theory describes how social capital operates through social networks and social institutions, 28 assumes that delinquency and crime occur in neighborhoods where social relations and social institutions have broken down, 30,31 and is characterized in communities by concentrated disadvantage (poverty), residential instability, and ethnic heterogeneity. 31 Although in this review indicators of community constructs associated with social disorganization theory were reported in the poor neighborhood support and cohesion table, social disorganization theory has been used in the literature to measure community support and connectedness as well as diminished economic opportunities and is a clear example of how indicators in 1 results table could be linked to multiple risk and protective factors.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, children who come from marginalized and minoritized groups may be more prone to structural and institutional strains or stressors, which, coupled with exposure to ACEs at home, may exacerbate the effects of ACEs on involvement with peers exhibiting negative behaviors (Shonkoff et al, 2021; Trinidad 2021b). Youth who are exposed to both structural disadvantages and chronic or frequent early ACEs at home may associate or join delinquent peer groups to receive support and respite from a stressful home environment (Bell, 2009; De La Rue & Espelage, 2014). Future research should continue to explore how early ACEs may work as a pathway to peer group formation, including the role of middle‐childhood mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…This reduction in conventional attachments can increase the likelihood that adolescents will encounter criminal groups, and it frees them to associate with such groups. For example, scholars have shown that adolescents who are rejected or mistreated by their family members sometimes associate with or join delinquent peer groups such as gangs to gain support or comfort that they cannot obtain at home (Bell, 2009; De La Rue & Espelage, 2014). Furthermore, stressed youth may also be rejected by conventional peers, which may increase their likelihood to gravitate toward unconventional or delinquent peers (Lansford et al, 2014).…”
Section: Aces and Delinquent Peer Associationmentioning
confidence: 99%